Investigation of LaVO3 based compounds as a photovoltaic absorber. (1st March 2018) - Jellite, M.; Rehspringer, J.-L.; Fazio, M.A.; Muller, D.; Schmerber, G.; Ferblantier, G.; Colis, S.; Dinia, A.; Sugiyama, M.; Slaoui, A.; Cavalcoli, D.; Fix, T.
Highlights: A material with an adjustable bandgap appropriate for photovoltaics is investigated. Three novel deposition techniques of LaVO3 are developed. The potential of LaVO3 is investigated in solar cell architectures. Abstract: Bulk LaVO3 (LVO) is known to provide an optical bandgap of 1.1 eV which is interesting for photovoltaic applications. Here, we compare the properties of LVO thin films using different techniques, namely pulsed laser deposition, spin coating by solgel and sputtering. ZnO/LVO p-n junctions were fabricated in order to obtain solar cell architectures. The grown films were analyzed with Surface photovoltage and Scanning Kelvin Probe Microscopy. The analysis of the junctions showed that the photogenerated electron-hole pairs are poorly separated and therefore not efficiently collected. LVO has shown the particularity to provide very high work function (4.6 eV) and a great dependence of the electrical and optical properties on the growth conditions, including the oxygen stoichiometry and the La/V ratio of the films.